HASIL DESTILASI KERING BEBERAPA JENIS KAYU INDONESIA - Tjutju Nurhayati Hartoyo (Jurnal Penelitian Hasil Hutan, 1988)
The  chemical  degradation of  wood  products  obtained by  destructive distillation in this  experiment are charcoal, pyroligneous liquor, wood tar and fuel gas. Pyroligneous  liquor  contains mainly water, acetic  acid and methanol. Wood tar is very complicated  phenolic  compound   and contains  creosote  oil  and pitch.The  results  of  destructive  distillation   of  45  wood  species  from  East  Kalimantan,   lrian  and  Maluku vary  widely. Charcoal yield ranged from 19.81to  41.24   percent,  pyroligneous     liqour  from  40.29   to  66.12 percent   and  the yield  tar  from  5.42  to  20.60 percent. Chemical  composition of  the distillates  indicated  that  acetic  acid content ranged from 1.19 to 9.53   percent, methanol ranged  from  0.22 to 3.75 percent,  phenol ranged from  0.10 to 1.62 percent   and pitch ranged  from  2.06 to 11.53  percent.The result  of  proximate    analysis  of  charcoal  indicated   that  moisture   content   ranged  from  1.12  to  6.85  percent, vovalite matter  from  11.29 to 29.20  percent  and ash ranged  from  0.23 to 7.11 percent.